The Mediating Role of Work Satisfaction in the Effect of Ethical Leadership on Employee Performance - Dino Manarso; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Through the utilisation of job satisfaction as a moderating factor for PT